Revolutionizing Customer Experience through Innovative Digital Marketing Approaches - Baddam, Parikshith Reddy (Global Disclosure of Economics and Business, 2022)
This study explores the transformative impact of innovative digital marketing approaches on revolutionizing customer experience in the contemporary business landscape. The study’s main objectives are to examine the role of personalization, immersive technologies, and omnichannel integration in enhancing customer engagement and satisfaction, analyze the effectiveness of measurement and analytics in evaluating digital marketing initiatives’ impact, and identify critical policy implications for businesses and policymakers. Utilizing a secondary data-based review approach, this study synthesizes insights from peer-reviewed academic journals, industry reports, and case studies to investigate emerging trends and best practices in digital marketing. Significant findings include the paramount importance of personalization in driving customer engagement, the considerable role of immersive technologies in creating memorable brand experiences, and the critical need for omnichannel integration to deliver seamless and cohesive customer experiences. Policy implications highlight the importance of privacy and data protection, digital inclusion, transparency in personalization efforts, and standardized measurement frameworks. Overall, this study underscores the transformative potential of innovative digital marketing approaches in shaping the future of customer experience.